Development & Validation of stress assessment scale for Maternity Nurses - Dr. Supriya Pottal Ray , Dr N Sujita Devi , Dr K Memchoubi (South Eastern European Journal of Public Health, 2025)
Background: Maternity & Obstetrical Nursing is a intriguing profession which is high in terms of accuracy, managing emergencies, increased accountability and responsibility. It makes it no less than being a demanding occupation with authority and liability. The midwife serves multiple roles while catering to a woman who may in her antenatal phase, labouring woman or woman enjoying motherhood. While the midwife deals with the woman, she is also accountable to the care of foetus & newborn. Hence a midwife is under pressure situations and needs to perform to the best of her abilities. Numerous studies are conducted on the stress level of Nurses as a whole, but very few literatures is available on the speciality area Nurses. These studies are essential to help Nurses cope up with stressors, identify coping strategies, it is equally essential to know the reasons and develop scale which are tailor made to identify the stress among Nurses from maternity unit. Methodology: Mixed method research design was adopted. The study was conducted in two phases. A quantitative research approach was adopted for the second phase of the study. Approval was received from IEC, BV (DU) CON, Pune. Non-probability purposive sampling technique was used to recruit samples in both the phases. For exploring the stress and coping strategies saturation of data was achieved with 20 Nurses who were working in the labor rooms, antenatal & postnatal wards of different hospitals form the city.In-depth interviews were conducted where the Nurses narrated the most stressful situations they have been through and the strategies they have adopted to face such situations in the near future. The verbatim was coded and themes were generated. Phase two consisted of identifying the factors & the coping strategies which gave rise to the development of Scale to assess stress among maternity nurses. The developed tool was validated by experts from the field of Obstetrics & Midwifery Nursing professionals, physicians and Nurse Practitioners. Result: Analysis of the qualitative arm was done by thematic content analysis which the emergence of 4 themes and 8 sub themes. The codes, sub themes & themes were studied and analyzed critically and stress scale was developed & validated. Themes which emerged from the in-depth interviews were Demanding situations and the efficiency of midwives, second theme framed was raised accountability & responsibility, third theme identified was hand holding to the juniors in crisis situation and the final theme was coping strategies adopted in pressure situations. Phase second involved the development of stress scale for Maternity Nurses , where a five point Likert scale was developed with items based on facing life threatening situations of mothers, conflicting situations with caretakers, mothers reluctance to treatment protocol, noncompliance of the laboring woman to procedures tool , uncertainty of the treatment plan, excessive workload, staff shortage. .Conclusion: Midwives get impacted by the stressful situation in the antenatal ward, most importantly the labor room, and postnatal wards especially with postnatal bereavement mothers. These situations are stressful for the midwives to handle. The junior midwives need hand holding and support while the senior midwives need to adopt coping strategies, administrators need to look for burnout among the nurse midwives. Hence stress scale developed needs to be utilized in assessing the stress level and identifying solutions for midwives in order to provide a encouraging and reassuring environment to contribute their best.